Assesment of Enterobiasis Influence on Child Developmen - Puch, Alicja E.; Sodowska, Henryka (Anthropological Review, 1983)
The present work is an attempt at presentation of assesment of an influence of a certain childhood disease on human physical development. To this end a prolonged and well defined ilness — enterobiasis was selected as its influence is long lasting and clearly concerns alimentation. Moreover the disease is widespread in Poland (it is the most frequent ailment of gastrointestinal tract). The material for present work comprised body measurements of 442 children aged 6-15 years from two Silesian communities (Paprocany and Cielnice). From among the whole group of children 97 suffering from enterobisis were selected. It has been found that children with enterobiasis have on the average smaller body dimensions than the apparently healthy children. Also variance of body dimensions was smaller in a group of diseased individuals. The author conclude that disappearance of enterobiasis from the studied group would cause increase of its body size by about 3.5% of standard deviation. It is hypothesised that decrease in frequency of childchood diseases would have been an important factor of secular trend in body size.